Promising effects of silver tungstate microcrystals on fibroblast human cells and three dimensional collagen matrix models: A novel non-cytotoxic material to fight oral disease - Haro Chávez, Natali Lisette [UNESP] (2018)
Silver tungstate (α-Ag2WO4) microcrystals have shown encouraging results regarding their antimicrobial activity. However, in addition to the promising outcomes in fighting oral disease, cytotoxic tests are mandatory for screening new materials for biological applications. Here, we developed a better understanding of the effects of microcrystals on the behavior of both human gingival fibroblast (HGF) cells and three-dimensional (3D) collagen matrices. To perform these experiments, the lowest concentration of α-Ag2WO4 capable of preventing the visible growth of Candida albicans (C. albicans) planktonic cells was defined as the test concentration, and it ranged from 0.781 (C1) to 7.81 (C2) to 78.1 (C3) μg/mL. Complete medium and lysis buffer (LB) served as negative (C−) and positive (C+) controls, respectively. The effect of the microcrystal concentration on the morphology, remodeling and proliferation of HGF cells was evaluated by different approaches. Quantitative and qualitative assessments demonstrated that α-Ag2WO4 did not affect the mitochondrial enzymatic activity of HGF cells cultured in a monolayer or the cell viability within 3D collagen matrices. These experiments showed that α-Ag2WO4 at the C2 concentration did not damage the genomic DNA. The development of new materials is attractive for the possible treatment of diseases and for avoiding indiscriminate prescribing of antibiotics. These findings provide information on the effect of α-Ag2WO4 on cell behavior and reveal that these microcrystals are non-cytotoxic against human gingival cells over a sufficient period to measure the hazard potential.